Analisis Tingkat Risiko Bahaya Kerja Menggunakan Meode Hazop (Hazard and Operability) pada PT. Madubaru PG/PS Madukismo - Muhammad Arifin; Ferida Yuamita (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
PT. Madubaru in every production process has hazard factors in the workplace in the form of physical properties, ergonomics, and work potential such as noise, fire, and explosions that may occur and can endanger the safety of workers. The purpose of this study is to determine the possibility of an event or impact from work accident hazards and to find out efforts to control or improve potential work accidents so that risk handling can be carried out quickly and accurately using the HAZOP (Hazard and Operability) method. Based on work accident data that occurred in the 2021 milling season, there were 18 work accidents. Through data processing using a risk assessment obtained from the likelyhood level analysis and the Severity level assessment, 7 values ​​of T risk (High) are obtained, namely at the floor study point with 4 of them occurring at the mill station, 7 S (medium) risk values ​​at the mill study point; sugarcane; gearbox; warehouse cranes; and grinding; 4 risk values ​​R (low) at the point of the jack review; hot water; mill 3; rotary handlebar. Improvements or control efforts that can be carried out on PG Madukismo are using PPE such as helmets, glasses, gloves, shoes to avoid or minimize work accidents, namely getting angry splashes, falling sugarcane, slipping, and being stung by animals such as centipedes. Then the addition of a warning system such as a label as a marker of danger in certain production areas. The warning system can help workers to always be careful in areas that cause work accidents.